Effect of some micronutrient application rates on yield and yield components of wheat in calcareous soil of the Iraqi Kurdistan Region - Rasul, Ghafoor Ahmed Mam; Ahmed, Sarkawet Taha; Maaruf, Karwan Fatah; Zorab, Zanyar Karim (Sulaimani Journal for Pure and Applied Sciences, 2018)
Wheat is the main essential cereal grain crop for food in the world. Management of nutrient is an important factor to increase its productivity. To evaluate the role of micronutrients in improving wheat yield, two field experiments were conducted by application of Zn, Cu, and Fe to the soil in individually and combined forms the source of micronutrients are ZnSO4, CuSO4 and Fe-EDDHA (Ethylenediamine Di-2-Hydroxyphenyl Acetate Ferric) 6% Fe. The number of treatments was thirteen treatments, and the experimental design is Randomized Complete Block Design (RCBD) with three replicates. Results showed that the application of Zn, Cu, and Fe in individually or combined forms were, not affected on the yield and yield components of wheat crop, except for plant height (cm), tillers per plant, 1000-grain weight (g) and harvest index from Bakrajow location While from Kanypanka location plant height (cm) and grain per spike were affected significantly.
Keywords: Micronutrients; Wheat yield; Calcareous soil and yield components